Analysis on Use of Open Educational Resources during EmergencyRemote Education due to Covid-19: A Case Study in Turkey - Ayşe Saliha Sunar; Esra Yükseltürk; İsmail Duru (SAGE Open, 2022)
During the mass curfews, travel bans, school shutdowns, face-to-face education was discontinued, and many universities had to urgently switch to online education. Academics, most of whom are not familiar with digital pedagogy, had to adapt their lectures to online learning. The aim of this study is to analyze how Open Educational Resources (OERs) are used in practice during emergency remote teaching (ERT) and whether this influences the regular practice of academics on a global level and in Turkey in the longer term. Methodologically, we adopt a mixed-methods approach in two stages: (i) an empirical study conducted in Turkey to find out what prior knowledge and experience academics have with OERs and how they use OERs during ERT; (ii) a complimentary desk study on the global situation of OER use. Our results show that academics who did not know about OERs before the pandemic are still hesitant to use them, even though they have prior experience with online teaching. In addition, academics with higher rank and academics in architecture, philology, and arts have the most negative opinion about campus education being fully accessible online.